THE DEVELOPMENT OF TPACK FOR ELEMENTARY SCHOOL TEACHERS IN USING CANVA APPLICATION - Rindanigsih, Ida; Zuhro, Sofiatuz (Antis Publisher, 2023)
The purpose of this study was to determine the development of TPACK competencies in elementary school teachers in using Canva application. To achieve this goal, this study used a library research method by studying and analyzing various scientific articles, especially those related to TPACK competencies in elementary school teachers using the Canva application. All cited scientific articles were retrieved from Mendeley and Google Scholar. This study found that the development of TPACK competencies in elementary school teachers through the use of Canva can have a positive impact in creating a more dynamic, innovative learning environment that supports the optimal development of students in this digital era and can meet students' learning needs visually.